2022
DOI: 10.1093/brain/awab317
|View full text |Cite
|
Sign up to set email alerts
|

Inactivating Celsr2 promotes motor axon fasciculation and regeneration in mouse and human

Abstract: Understanding new modulators of axon regeneration is central to neural repair. Our previous work demonstrated critical roles of atypical cadherin Celsr2 during neural development, including cilia organization, neuron migration and axon navigation. Here, we address its role in axon regeneration. We show that Celsr2 is highly expressed in both mouse and human spinal motoneurons. Celsr2 knockout promotes axon regeneration and fasciculation in mouse cultured spinal explants. Similarly, cultured Celsr2 mutant moton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…The decrease of reactive astrocytes in Celsr2 −/− injured spinal cords was mainly found at day 14 and 21 after BPA, and the direct effect of Celsr2 inactivation on astrocytes could not be excluded. In our study, Celsr2 −/− mice have better axon regeneration and functional recovery after BPA, and this outcome may attribute to two explanations: firstly, Celsr2 inactivation benefits neuronal survival through regulating synaptic stripping in the present work, which alleviates the excitotoxicity on injured motoneurons to facilitate their survival; secondly, Celsr2 inactivation elevates small GTPases in injured motoneurons to enhance their regeneration ability in the previous report [36,47].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The decrease of reactive astrocytes in Celsr2 −/− injured spinal cords was mainly found at day 14 and 21 after BPA, and the direct effect of Celsr2 inactivation on astrocytes could not be excluded. In our study, Celsr2 −/− mice have better axon regeneration and functional recovery after BPA, and this outcome may attribute to two explanations: firstly, Celsr2 inactivation benefits neuronal survival through regulating synaptic stripping in the present work, which alleviates the excitotoxicity on injured motoneurons to facilitate their survival; secondly, Celsr2 inactivation elevates small GTPases in injured motoneurons to enhance their regeneration ability in the previous report [36,47].…”
Section: Discussionsupporting
confidence: 56%
“…In the ventral horn, motoneurons receive inhibitory and excitatory inputs from spinal segmental interneurons. Our previous studies showed that all spinal motoneurons were expressed by Celsr2 [ 36 ]. Using Celsr2 LacZ mice, in which Celsr2 expression could be visualized by β-gal signal, we found that Parvalbumin-positive, Calretinin-positive GABAergic, and CamKII-positive glutamatergic interneurons co-expressed Celsr2 in the ventral horn using double immunostaining (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The significant bQTL for last week mean 30% choice on Chr 3 had four notable genes, including Celsr2 and Sypl2 , which both had coding sequence variants, and Eps8l3 and Gstm5 , which had association data in GWAS Catalog with alcohol-associated traits (Table 4). Celsr2 encodes a transmembrane protein and has been implicated in axon development in the forebrain[54] and regulation of motor neuron regeneration following injury [55]. Sypl2 encodes a synaptophysin-like protein, but remains relatively uncharacterized; however, it has been implicated in obesity [56, 57] and major depressive disorder [58] in human GWAS literature.…”
Section: Discussionmentioning
confidence: 99%
“…Both CELSR2 and CELSR3 are implicated in dendrite morphogenesis. CELSR2, a core component of PCP signaling, controls motor axon regeneration through GTP-bound Rac1, Cdc42, JNK, and c-Jun signaling (Wen et al, 2022). Downregulation of CELSR2 in brain slices reduces the length of dendrites in cortical pyramidal neurons and the complexity of dendritic trees of Purkinje cells, whereas silencing of CELSR3 leads to dendritic overgrowth (Shima et al, 2002(Shima et al, , 2004(Shima et al, , 2007.…”
Section: Role In Neurogenesismentioning
confidence: 99%